The Effect of Fraud Pentagon on Earnings Management with the Audit Committee as a Moderating Variable - Wulandari, Putri Cahya; Wawo, Andi; Juardi, Muhammad Sapril Sardi (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to determine the effect of the fraud pentagon consisting of pressure, opportunity, rationalization, competence, and arrogance on earnings management with the audit committee as a moderating variable. This research uses annual report data from 30 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Quantitative research method with a causality approach using SPSS (Statistical Program for Social Science) software or application in hypothesis testing. The results obtained show that pressure has a significant and negatif effect on earnings management. The opportunity, rationalization and competence variables have a positive effect on earnings management. The arrogance variable has no effect on earnings management. Furthermore, the audit committee is unable to moderate the influence of pressure, opportunity, rationalization, competence and arrogance on earnings management. Keywords : Fraud Pentagon Theory, Komite Audit, Manajemen Laba